The Physical Properties and Crystallization Kinetics of Biocomposite Films Based on PLLA and Spent Coffee Grounds - Novák, Jan; Běhálek, Luboš; Borůvka, Martin; Lenfeld, Petr (Materials (Basel, Switzerland), 2022)
In the context of today's needs for environmental sustainability, it is important to develop new materials that are based on renewable resources and biodegrade at the end of their life. Bioplastics reinforced by agricultural waste have the potential to cause a revolution in many industrial applications. This paper reports the physical properties and crystallization kinetics of biocomposite films based on poly(L-lactic acid) (PLLA) and 10 wt.% of spent coffee grounds (SCG). To enhance adhesion between the PLLA matrix and SCG particles, a compatibilizing agent based on itaconic anhydride (IA)-grafted PLLA (PLLA-g-IA) was prepared by reactive extrusion using dicumyl peroxide (DCP). Furthermore, due to the intended application of the film in the packaging industry, the organic plasticizer acetyl tributyl citrate (ATBC) is used to improve processing and increase ductility. The crystallization behavior and thermal properties were observed by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Crystallinity degree increased from 3,5 (neat PLLA) up to 48% (PLLA/PLLA-g-IA/ATBC/SCG) at the highest cooling rate. The physical properties were evaluated by tensile testing and dynamic mechanical analysis (DMA). The combination of the compatibilizer, SCG, and ATBC led to a synergistic effect that positively influenced the supramolecular structure, internal damping, and overall ductility of the composite films.
Keywords: poly(L-lactic acid); biocomposites; itaconic anhydride; spent coffee grounds; plasticizer